2012
DOI: 10.1177/1474651411429906
|View full text |Cite
|
Sign up to set email alerts
|

Through-knee amputation in peripheral vascular disease

Abstract: T hrough-knee amputation accounts for just 2.8% of annual amputations in England. Traditionally it is viewed as an operation with poor outcomes, and its use limited. We present a case series and review of articles published on through knee amputation.The literature review covers the 17 papers identified on through-knee amputation in peripheral vascular disease. The results are summarised and discussed, with favourable outcomes in terms of perioperative mortality and primary healing demonstrated in the majority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…There were no controlled trials found (level 1), with 11 observational studies (level 2) 8,34,38,42,45,47–52 and 6 non-analytical studies (level 3). 5,15,26,43,44,46 Seven studies had a high risk of bias (−), 5,8,34,42,43,46,52 eight studies had a low risk of bias (+) 15,26,38,44,45,47,4951 and only one study had a very low risk of bias (++). 48 Most of the studies were retrospective with only four prospective studies, 8,47,48,51 and it was due to the retrospective nature that a higher quality grading (++) could not be given in four other studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There were no controlled trials found (level 1), with 11 observational studies (level 2) 8,34,38,42,45,47–52 and 6 non-analytical studies (level 3). 5,15,26,43,44,46 Seven studies had a high risk of bias (−), 5,8,34,42,43,46,52 eight studies had a low risk of bias (+) 15,26,38,44,45,47,4951 and only one study had a very low risk of bias (++). 48 Most of the studies were retrospective with only four prospective studies, 8,47,48,51 and it was due to the retrospective nature that a higher quality grading (++) could not be given in four other studies.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies used clinical judgments to determine the appropriate amputation level, 5,15,26,4246,51 none of the studies utilised physiological tests and three studies did not indicate the method of assessment. 34,50,52 The number of identified variables/confounders that affect wound healing ranged from 0 to 5 among the studies, but only one study analysed how the variables influenced the results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations